Estudo teórico das propriedades eletrônicas e ópticas em nanofitas de SnO2 - Campos, Bruno De Oliveira (2014)
In this work we calculate the optical and electronic characteristics of tin dioxide nanoribbons (SnO2) and pure oxygen vacancy, and the changes in the structures and properties, which occurred in the same; using as a tool the first-principles calculations, based on the method Theory Density Functional (DFT). Using the SIESTA code in our simulations, using some approximations necessary, which will be described. Through the SIESTA calculate the dielectric functions, real and imaginary parts, and means calculate some optical properties such as absorption coefficient, reflectance and other optical conductivity. The study of the electronic properties of the structures was through the electronic band structure, the total state density (DOS) of the partial density of state (PDOS), calculating the resulting magnetic moment and of the study of contour map of the difference of electron density. The results are compared to experimental studies, appear satisfactory, where some results are in agreement with other studies in the literature.